The Relationship between Knowledge Level and Self-Medication Behavior for Scabies at SMK Plus Al-Istiqomah - Sadino, Asman; Suwandi, Deden Winda; Susanti, Risa; Nuari, Doni Anshar; Renggana, Hesti; Rohimah, Vina Siti; Apriliani, Nisa Siti (Indonesian Journal of Community Empowerment (IJCE), 2024)
Scabies is a skin disease that is often ignored. Scabies is still common in Islamic boarding schools with a high prevalence rate. Self-medication is used to treat mild to moderate illnesses without consulting a doctor first. This community service aims to determine the relationship between the level of understanding of scabies' self-medication behavior at SMK Plus Al Istiqomah. The method used begins with the distribution of an initial questionnaire (pre-test), presentation of the material with the help of PowerPoint slides, a question and answer session between students (i) and the presenter, and distribution of the final questionnaire (post-test). The results of this community service activity showed an increase in knowledge of scabies from a percentage of 5% to 87.5%. This means that the education provided can be well received by students at SMK Plus Al-Istiqomah.